2020
DOI: 10.1136/emermed-2020-210512
|View full text |Cite
|
Sign up to set email alerts
|

Beirut: a wounded city explodes

Abstract: NF: An intense boom thundered through the city and with it, buildings shook, glass windows shattered and structures collapsed. The ripples could be heard and felt by people living as far as 10 and 20 miles away from the traumatised city. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study set out to explore the prevalence of PTSD and associated mental health problems (depression, anxiety, and stress) following the Beirut Port explosion on August 4, 2020, which took the lives of more than 200 people and injured more than 6,000 (Maamari et al, 2020). Our results indicated that 40% of men and 47% of women reported clinically significant symptoms of PTSD, and further gender differences were evident for depression, anxiety, and stress with women scoring higher across these measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study set out to explore the prevalence of PTSD and associated mental health problems (depression, anxiety, and stress) following the Beirut Port explosion on August 4, 2020, which took the lives of more than 200 people and injured more than 6,000 (Maamari et al, 2020). Our results indicated that 40% of men and 47% of women reported clinically significant symptoms of PTSD, and further gender differences were evident for depression, anxiety, and stress with women scoring higher across these measures.…”
Section: Discussionmentioning
confidence: 99%
“…On the 4th of August 2020, part of a consignment containing 2,700 kg of ammonium nitrate stored in a warehouse at the Beirut Port exploded, devastating much of the city (Rigby et al, 2020). The explosion resulted in the death of more than 200 individuals, over 6,000 individuals were injured, and approximately 300,000 people were made homeless (Maamari et al, 2020; Rigby et al, 2020). Such disasters are likely to result in community-level economic, social, and mental health costs (Lee et al, 2020).…”
Section: Demographic Correlates Of Ptsd Symptomatologymentioning
confidence: 99%